(untitled) (Pedagogical Horizons, 2025)
Liberal democracies are on the brink. Some voters support the transformation of democracy into autocracy, other citizens are worried about it. This article discusses democracy talks – streetworking for democracy – as a low-threshold approach of civic education in public spaces. Based on a specific grassroot-initiative, it describes and analyzes the conditions, possibilities, and practices for strengthening democratic attitudes and political forces using the dialogue method. The result: the concept of democracy cannot remain abstractly institutional and procedural in discussion formats, but must be approached from a daily life perspective. Streetworking for democracy is more than just listening; statements that reject democracy and are hostile to social groups must be contradicted. This requires time, passion, and further training.